Antimicrobial and antitubercular activity of novel pyrazole-4-carboxamide derivatives: Synthesis and characterization - C. Asha Deepthi, J. Prathyusha (Journal of Applied Pharmaceutical Science, 2023)
A corrigendum is published for this article and available here: https://japsonline.com/abstract.php?article_id=4026&sts=2The current research aims to identify the newest class of antifungal, antibacterial, and antitubercular lead compounds. Through the use of a carboxamide linkage, recent research has designed and synthesized a unique class of pyrazole-based molecular hybrids of aryl amines. Using a multistep method, the desired pyrazole carboxamide derivative was prepared. Compounds were characterized using 1HNMR, C13 NMR, and MASS spectral techniques. These substances were tested for their ability as antibacterial, antifungal, and antitubercular agents. All the compounds tested against Gram-positive and Gram-negative pathogens and fungal strains showed good antibacterial activity. Against Gram-positive pathogens, compound 5i showed potent activity, compound 5k demonstrated potent activity against Gram-negative strains, and compounds 5a, 5i, and 5j established potent activity against fungal strains and the Mycobacterium tuberculosis H37Rv strain.